Interleukin‐1α induced release of interleukin‐8 by human bronchial epithelial cells in vitro: assessing mechanisms and possible treatment options. (2nd March 2017) - Bellon, Hannelore; Vandermeulen, Elly; Mathyssen, Carolien; Sacreas, Annelore; Verleden, Stijn E; Heigl, Tobias; Vriens, Hanne; Lammertyn, Elise; Pilette, Charles; Hoet, Peter; Vos, Robin; Vanaudenaerde, Bart M; et al.
Summary: Survival after lung transplantation is hampered by chronic lung allograft dysfunction (CLAD). Persistently elevated BAL‐neutrophilia is observed in some patients despite treatment with azithromycin, which may be induced by IL‐1α. Our aim is to establish an in vitro model, assess mechanistic pathways and test different therapeutic strategies of IL‐1α‐induced release of IL‐8 by human bronchial epithelial cells. Bronchial epithelial cells (16HBE) were stimulated with IL‐1α with or without azithromycin or dexamethasone. IL‐8 protein was analyzed in cell supernatant. Different MAP kinases (p38, JNK, ERK 1/2, Iκβ) and targets known to be involved in tumor formation (PI3K, Akt) were investigated. Finally, different treatment options were tested for their potential inhibitory effect. IL‐1α induced IL‐8 in bronchial epithelial cells, which was dose‐dependently inhibited by dexamethasone but not by azithromycin. IL‐1α induced p38 and Akt phosphorylation, but activation of these MAPK was not inhibited by dexamethasone. JNK, ERK 1/2, Iκβ and PI3K were not activated. None of the tested drugs reduced the IL‐1α induced IL‐8 production. We established an in vitro model wherein steroids inhibit the IL‐1α‐induced IL‐8 production, while azithromycin was ineffective. Despite using this simple in vitro model, we could not identify a new treatment option for azithromycin‐resistant airway neutrophilia.